2018
DOI: 10.3892/ol.2018.8227
|View full text |Cite
|
Sign up to set email alerts
|

CDH2 expression is of prognostic significance in glioma and predicts the efficacy of temozolomide therapy in patients with glioblasotma

Abstract: Glioma is the most common and malignant primary brain cancer in adults. Radical surgical excision accompanied by radiotherapy and chemotherapy is the prevailing standard therapy for patients with glioblastoma (GBM). Cadherin 2 (CDH2) encodes the N-cadherin protein, a classical cadherin and a member of the cadherin superfamily, which sustains the integrity of the cell and is involved in several cell signal transduction pathways. In the present study, the association between CDH2 expression and clinical features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
(24 reference statements)
0
29
0
Order By: Relevance
“…In addition, down regulation of CCND1 may be an important mechanism by which everolimus increases the therapeutic window of paclitaxel in cervical cancers ( Yilmaz et al, 2016 ). The biological role of cadherin 2 (CDH2) was also mostly reported in glioma with prognostic significance ( Chen, Cai & Jiang, 2018 ). Previous studies showed that chemokine (C-X-C motif) ligand 12 (CXCL12) had reported in different human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, down regulation of CCND1 may be an important mechanism by which everolimus increases the therapeutic window of paclitaxel in cervical cancers ( Yilmaz et al, 2016 ). The biological role of cadherin 2 (CDH2) was also mostly reported in glioma with prognostic significance ( Chen, Cai & Jiang, 2018 ). Previous studies showed that chemokine (C-X-C motif) ligand 12 (CXCL12) had reported in different human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that CDH2 is closely related to glioma tumor grade after analyzing data from a glioma cohort constructed through multiple public data banks. The prognostic analysis shows that high CDH2 expression is closely related to poor glioma prognoses and that there is no subsequent bene t obtained from temozolomide treatment [25]. Zhou et al found that CDH2 can signi cantly promote angiogenesis in lung adenocarcinoma (LUAD) and participate in regulating the sensitivity of angiogenesis antagonists [26].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is not much research on the role of ITIH2 in tumor growth and metastasis, which is also a potential direction for the study of tumor metastasis mechanism in the future CDH2 is a member of the cadherin family, which regulates many cellular processes including apoptosis, angiogenesis, and chemoresistance (Miao, Wang et al 2018). CDH2 is up-regulated in many kinds of cancers, including colorectal cancer , prostate cancer (Zhang, Shen et al 2014), gastric cancer , bladder cancer (van der Horst, Bos et al 2014), lung cancer (Zhu 2015) and glioma (Chen, Cai et al 2018). Moreover, it is reported that CDH2 play an important role in the process of epithelia-mesenchymal transition (Yang, Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the lung cancer research, it was found that CDH2 expression is associated the ge tinib-resistance (Yamauchi 2011) and to the brain metastases of lung cancer cells (Grinberg-Rashi, Ofek et al 2009). In glioma, CDH2 is recognized as a independent prognostic factor and its high expression is correlated with high-grade glioma and worse outcome (Chen, Cai et al 2018).…”
Section: Discussionmentioning
confidence: 99%